Dissolution kinetics of coal and limestone samples from Kogi state, Nigeria - Anthony Ugbedeojo Atumeyi; Adams Udoji Itodo; Rufus Sha'Ato; Raymond Ahulle Wuana (African Scientific Reports)
This work is concerned with the dissolution behaviour and kinetics of Okobo coal and Obajana limestone from Kogi State, Nigeria, within acidic, basic, and neutral media. This was achieved using hydrochloric acid and sodium hydroxide with distilled water, representing acidic, basic and neutral environment respectively, where the rates were determined for six hours. Overall, the dissolution rates were significantly enhanced under an acidic medium for both minerals, indicating a maximum dissolution of 6.1% for Okobo coal, as depicted in results, and 7.7% dissolution in the case of Obajana limestone. Basic media provided moderated dissolution, while the water had minimum effects. The kinetic analysis using zero-order and Higuchi models indicated that the zero-order best fitted coal dissolution in acidic condition, but for limestone, both the models were fitted very well. These results would provide a good knowledge to the mineral industry, environmental management, and building industries through the conditions of favoring mineral decomposition and utilization.